2015
DOI: 10.3765/salt.v0i0.2656
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for counting: A unified semantics for measure terms and classifiers

Abstract: This paper develops and extends the semantic account of morphological number marking in the presence of numerals from Scontras 2013. The account handles variation in patterns of number marking along two dimensions: crosslinguistically, between languages that either necessitate or prohibit singular morphology in the presence of numerals greater than 'one'; and within one and the same language: English. The proposed semantics accounts for both sorts of variation by assuming flexibility in the selection of the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…Finding sensitivity to both singular and plural agreement errors, we concluded that number in the native baseline is a multi-valued feature (both singular and plural are specified feature values; cf. Sauerland 2003;Scontras 2013a;. Finding sensitivity only to agreement errors involving feminine adjectives, we concluded that gender is single-valued (feminine is the specified feature value, while masculine serves as the absence of gender specification, consistent with the classic analysis proposed by Harris 1991; see also Kramer 2015).…”
supporting
confidence: 83%
“…Finding sensitivity to both singular and plural agreement errors, we concluded that number in the native baseline is a multi-valued feature (both singular and plural are specified feature values; cf. Sauerland 2003;Scontras 2013a;. Finding sensitivity only to agreement errors involving feminine adjectives, we concluded that gender is single-valued (feminine is the specified feature value, while masculine serves as the absence of gender specification, consistent with the classic analysis proposed by Harris 1991; see also Kramer 2015).…”
supporting
confidence: 83%
“…With respect to number marking, we follow Krifka (1989); Sauerland (2003); Scontras (2013Scontras ( , 2014 and assume the separation of morpho-syntactic number from semantically interpretable number. Morpho-syntactic number is the result of uninterpretable agreement between a probing Num head and a goal NP: Agree(Num,NP).…”
Section: Preliminariesmentioning
confidence: 99%
“…In the semantic literature, it is commonly assumed that the distinction between obligatory classifier languages such as Mandarin and non-classifier languages such as English is due to a difference in the semantics of nouns (e.g., Chierchia 1998Chierchia , 2010Borer 2005;Rothstein 2010;Li 2011;Scontras 2013). According to this standard approach, all nouns in classifier languages are mass-like in the sense that they have uncountable denotations.…”
Section: Classifiers and Nominal Denotationsmentioning
confidence: 99%